2021
DOI: 10.1017/s1368980021002007
|View full text |Cite
|
Sign up to set email alerts
|

False and misleading health-related claims in food supplements on Spanish radio: an analysis from a European Regulatory Framework

Abstract: Objective: The excessive growth of the food supplements’ industry highlights the need to focus attention on all aspects involved in their proper consumption; one that takes centre stage is advertising. The aim of this research is to analyse the presence of false and misleading claims in food supplements advertising. To this end, a relationship is established between the different types of health-related claims and the substances on which they are based, whether authorised or not by EFSA. Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…It is well‐known that the current food market in these two countries is full of both unhealthy and healthy foods. Moreover, the glut of contradicting or misleading nutrition information from the internet, TV or paper media in modern society has caused confusion for the public 50–52 . Hence, there is a great need for authorised and comprehensive nutrition education to be provided for Chinese people to help them make informed food choices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well‐known that the current food market in these two countries is full of both unhealthy and healthy foods. Moreover, the glut of contradicting or misleading nutrition information from the internet, TV or paper media in modern society has caused confusion for the public 50–52 . Hence, there is a great need for authorised and comprehensive nutrition education to be provided for Chinese people to help them make informed food choices.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the glut of contradicting or misleading nutrition information from the internet, TV or paper media in modern society has caused confusion for the public. [50][51][52] Hence, there is a great need for authorised and comprehensive nutrition education to be provided for Chinese people to help them make informed food choices. Chinese people's mindset about nutrition concepts is unique.…”
Section: Intrapersonal Factors (Personal Perceptions/ Beliefs/attitudes)mentioning
confidence: 99%
“…The hypothetical setting can happen in the real world. A lot of dietary supplements implicitly claim to have efficacy in the treatment of diseases, and patients use these products for the treatment of diseases [ 2 , 8 , 9 , 25 ]. In addition to attractive health claims, more dietary supplement users including patients (Both and DS) thought “It is safe because it is food” “It is safe because it is made from natural ingredients or herbs” and “It has fewer side effects than medicines” compared to non-users (PM and None) in this study ( Table 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…The health claims of dietary supplements are regulated in each country, and claims for treatment diseases are prohibited in common [ 7 ]. So, most dietary supplements implicitly claim to have efficacy in treatment of diseases, and these claims mislead consumers to use dietary supplements for the treatment of diseases [ 8 , 9 ]. In addition, it is reported that many ingredients of dietary supplements, especially botanicals, have the potential to interact with drugs [ 10 , 11 ], and their concomitant use can cause serious adverse events [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is crucial to understand exactly what the claims on DS mean ( American Cancer Society, 2021 ). The claims should be true and not misleading 2 ( Muela-Molina et al, 2021 ). When they are not, there is good reason for concern about consumer safety ( Binns et al, 2018 ; Crawford et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%